Effect of Vitamin D3 on Untreated Graves’ Disease with Vitamin D Deficiency - Alhuzaim, Omar N (Libertas Academica, 2014)
OBJECTIVE: Besides its classical role in calcium and bone homeostasis, vitamin D is considered a potent immunomodulator that can affect the pathogenesis of several autoimmune diseases. Our aim is to evaluate the effect of vitamin D correction to a patient with new onset Graves’ disease (GD) with an underlying vitamin D deficiency. METHOD: We describe the effect of vitamin D3 on untreated Graves’ disease with vitamin D deficiency. RESULTS: A healthy Saudi woman in her 40s sought consultation with a three-month history of palpitation. She denied any history of heat intolerance, weight loss, menstrual irregularity or sweating. She has a history of chronic muscle aches and pains. Physical examination revealed a mild diffusely enlarged and non-tender thyroid gland with no bruit. She had no signs of Graves’ ophthalmopathy. In laboratory examinations, the initial thyroid function test, which was done in an outside hospital, revealed a TSH, 0.01 mIU/L; FT4, 22.5 pmol/L and FT3, 6.5 pmol/L. Vitamin D 25-OH level was done in our hospital and showed a result of 26.0 nmol/L with a TSH, 0.013 mIU/L; FT4, 16.7 pmol/L; and FT3, 3.8 pmol/L. TSH receptor antibody was positive. TC-99 m thyroid scintigraphy demonstrated an enlarged thyroid gland with increased radiotracer trapping and heterogeneous distribution. The patient was given only oral cholecalciferol 4000 IU per day since November 2012 (prescribed by an outside hospital) then from May 2013 onwards she was given 50,000 IU per month. Follow-up laboratory exams revealed improved vitamin D levels as well as TSH and FT4. She eventually improved both clinically and biochemically with a satisfactory outcome. CONCLUSION: Vitamin D deficiency may exacerbate the onset and/or development of GD and correction of the deficiency may be able to reverse it. However, further prospective clinical studies will be needed to define the role of vitamin D treatment in GD.